Numerical simulation of slipstreams and wake flows of trains with different nose lengths passing through a tunnel. (February 2021) - Meng, Shuang; Li, Xianli; Chen, Guang; Zhou, Dan; Chen, Zhengwei; Krajnovic, Siniša
Abstract: This study examined the slipstreams induced by high-speed trains (HSTs) passing through a tunnel using the improved delayed detached eddy simulation (IDDES) method. First, the flow fields in the open air and in a tunnel were compared. Furthermore, the flow in a tunnel was analyzed in detail, considering the development of both instantaneous flow structures and slipstream profiles at various measurement points. Finally, by considering four different nose lengths (4 m, 7 m, 9 m, and 12 m), the differences in the slipstream profiles and the wake flow induced by HSTs passing through a tunnel were determined. The results show that the piston effect had a significant influence on the slipstream profiles, causing a larger positive peak when a train passed through a tunnel. The peaks of the slipstream profiles decrease as the distances from the center of the track (COT) and the top of the rail (TOR) increases. The results show that a long nose length can reduce the scale and strength of the instantaneous x -vorticity and y -vorticity in the wake propagation region, thereby lowering the maximum slipstream peaks. The 12-m nose length train induced 56.7% lower velocity than the 4-m nose length train at y = 2 m beside the COT and z = 0.2 m above the TOR. In particular, the standard deviations of the positive peaks of the seven cross-sections decrease by 38.4% with the increase in the nose length from 4 m to 12 m, which means that a longer nose length can reduce the turbulence level in the wake propagation region. Consequently, from the perspectives of the safety and comfort of trackside people, a long nose length train is strongly recommended.